2017
DOI: 10.1016/j.scr.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of functional duplicity of Nestin expression in the adult mouse midbrain

Abstract: Whether or not neurogenesis occurs in the adult substantia nigra pars compacta (SNc) is an important question relevant for developing better treatments for the motor symptoms of Parkinson's disease (PD). Although controversial, it is generally believed that dividing cells here remain undifferentiated or differentiate into glia, not neurons. However, there is a suggestion that Nestin-expressing neural precursor cells (NPCs) in the adult SNc have a propensity to differentiate into neurons, which we sought to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
0
6
0
4
Order By: Relevance
“…Further, time-course analyses did not reveal classical neurogenesis evidenced by place of birth, neuronal differentiation, maturation and integration, raising the possibility that some mature neurons may express Nestin in midbrain [ 99 ]. Others have found hints of differentiation by means of cell growth and higher levels of expression of mature neuronal genes over long periods, albeit low proliferative rate and no evidence of migration [ 100 ]. Interestingly, single-cell gene expression data suggested that up-regulation of mature neuronal genes in Nestin - cre ERT2 -traced midbrain cells occurs over several months, not days, providing robust evidence for presence of Nestin + neural progenitors in adult midbrain.…”
Section: Role Of Nestin + Cells In Pathogenesis Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, time-course analyses did not reveal classical neurogenesis evidenced by place of birth, neuronal differentiation, maturation and integration, raising the possibility that some mature neurons may express Nestin in midbrain [ 99 ]. Others have found hints of differentiation by means of cell growth and higher levels of expression of mature neuronal genes over long periods, albeit low proliferative rate and no evidence of migration [ 100 ]. Interestingly, single-cell gene expression data suggested that up-regulation of mature neuronal genes in Nestin - cre ERT2 -traced midbrain cells occurs over several months, not days, providing robust evidence for presence of Nestin + neural progenitors in adult midbrain.…”
Section: Role Of Nestin + Cells In Pathogenesis Anmentioning
confidence: 99%
“…Remarkably, 4 days after tamoxifen many Nestin - cre ERT2 -traced cells have mature neuronal morphology, and are positive for both neuronal nuclear antigen and the pluripotency marker Sox-2. This short timeframe may be not enough for Nestin + progenitors to become mature neurons, again raising the possibility that mature neurons express Nestin and other immature genes under certain conditions and in contexts that may be not neurogenic [ 100 ]. Other authors have selectively deleted tyrosine hydroxylase in Nestin- or Sox-2-traced cells using cre ERT2 systems.…”
Section: Role Of Nestin + Cells In Pathogenesis Anmentioning
confidence: 99%
“…Although neurogenesis is a complex process regulated by a vast array of molecules, the functional heterogeneity of many of these regulators make them ill-suited to attempting to modulate neurogenesis without altering other forms of plasticity in multiple brain regions. For instance, neurotrophins such as brainderived neurotrophic factor, permissive plasticity factors such as polysialylated neural cell adhesion molecule, and even other stem-cell markers like nestin, while crucial to neurogenic function, also appear to regulate diverse forms of plasticity in other brain areas (Guirado et al 2014;Ehrlich and Josselyn 2016;Farzanehfar et al 2017). Conversely, the highly regionalized nature of TLX expression in the adult brain makes this transcription factor an attractive candidate for future studies on its role in mediating neurogenesis directly and specifically, particularly in light of recent evidence suggesting that TLX may be a point of crosstalk between the neuroinflammatory response and reductions in hippocampal neurogenesis observed following stress (Ryan et al 2013).…”
Section: Tlxmentioning
confidence: 99%
“…Nestin mRNA in neurons would be an indicator that nestin is actually being translated in early neurons. Several paper have described nestin mRNA in neurons in developmental, normal adult, and pathological/injury contexts (Crino & Eberwine 1996;Zhu et al 2011;Kuo et al 2005;Arner et al 2015;Perry et al 2012;Farzanehfar, Lu, et al 2017;Dey et al 2017;Farzanehfar, Horne, et al 2017;Bigler et al 2017), thus nestin expression is not excluded from neurons. Nestin's presence in subpopulations of adult neurons suggests that some neurons may never lose nestin expression, or may regain it later.…”
Section: Discussionmentioning
confidence: 99%